The clinical utility of tissue polymerase chain reaction, tissue culture, and tissue histology in blood-culture negative infective endocarditis - a South African single hospital experience - Endres, Wilhelm (Department of Medicine, 2025)
Background. Infective endocarditis (IE) poses significant diagnostic and therapeutic challenges, especially in blood culture-negative infective endocarditis (BCNIE) cases. Appropriate antimicrobial therapy is guided by knowledge of the causative organisms and their characteristics. Amongst patients undergoing surgery for IE, valve tissue may be evaluated for additional microbiologic information by performing broad range 16S ribosomal deoxyribonucleic acid (rDNA) polymerase chain reaction (PCR), tissue culture, and tissue histopathology. In patients with BCNIE, these diagnostic tests may identify the causative agents, guide further clinical management and improve local IE-related epidemiological data. The clinical utility of additional analysis of explanted tissue in a local South African setting has yet to be described. Objectives. This study aims to assess the clinical utility of performing PCR, culture, and histopathology on the tissue of surgically explanted valves in BCNIE patients in a South African public sector hospital. We assess their diagnostic yield and treatment impact in a cohort of BCNIE patients treated with empiric antibiotic regimens. Methods. We analysed data from the Groote Schuur Hospital (GSH) Infective Endocarditis Registry, a prospective observational study of adult patients with infective endocarditis. Participants for this analysis were selected based on clinical and pathological criteria for IE and negative blood cultures. All participants were treated between January 2017 to March 2021. During this study there was no set protocol for performing serum serology, and the treating clinicians determined empiric antibiotic regimens. Results. During the study period, we identified 165 IE cases, 57 (34.5%) of which were blood-culture negative. BCNIE patients had a mean age (±standard deviation) of 40.2 (13.4) years, and 41 (71.9%) were male. Twenty-seven of the 57 BCNIE patients underwent cardiac surgery and had tissue analysis performed. Tissue PCR identified an etiologic agent in 17/27 (63%) cases with Bartonella spp. (12/27, 44%) being the most common organism. Tissue culture was positive in 3/27 (11%), but the organisms identified were thought to reflect sample contamination. Tissue histopathology was performed in 22/27 (81.5%) cases and provided macroscopic confirmation of endocarditis but did not identify any specific organisms in any of the specimens. Only a small subset of 11 (19.3%) patients had serum serology for Bartonella spp. and Coxiella spp. performed, 5/11 (45.5%) were positive for Bartonella spp. There was a 100% concordance rate between positive serum serology and tissue PCR. Tissue PCR impacted the antimicrobial regimen in 20/27 (74%) cases. Tissue culture and tissue histopathology did not influence antibiotic regimens in any patients. Conclusion. The most common BCNIE causative organism identified by additional non-culture testing in our setting is Bartonella spp. The yield from tissue culture was poor. Histopathology was not useful for etiological identification. The study suggests an underutilisation of preoperative serum serological testing in our setting. Tissue PCR influenced the management in a significant proportion of patients and may be important in all BCNIE cases. In light of the significant limitations of this study, an appropriately designed local prospective study to better understand the role of tissue PCR and serum serology in evaluating and treating BCNIE is warranted.